Combining 3D single molecule localization strategies for reproducible bioimaging - Clément Cabriel; Nicolas Bourg; Pierre Jouchet; Guillaume Dupuis; Christophe Leterrier; Aurélie Baron; Marie‐Ange Badet‐Denisot; Boris Vauzeilles; Emmanuel Fort; Sandrine Lévêque‐Fort (2019)
Abstract Here, we present a 3D localization-based super-resolution technique providing a slowly varying localization precision over a 1 μm range with precisions down to 15 nm. The axial localization is performed through a combination of point spread function (PSF) shaping and supercritical angle fluorescence (SAF), which yields absolute axial information. Using a dual-view scheme, the axial detection is decoupled from the lateral detection and optimized independently to provide a weakly anisotropic 3D resolution over the imaging range. This method can be readily implemented on most homemade PSF shaping setups and provides drift-free, tilt-insensitive and achromatic results. Its insensitivity to these unavoidable experimental biases is especially adapted for multicolor 3D super-resolution microscopy, as we demonstrate by imaging cell cytoskeleton, living bacteria membranes and axon periodic submembrane scaffolds. We further illustrate the interest of the technique for biological multicolor imaging over a several-μm range by direct merging of multiple acquisitions at different depths.